IS RESEARCH IN BIBLIOTECOLOGY POSIBLE? - Contreras Contreras, Fortunato (2006)
Sorne problems hindering proper research in Bibliotecology in Peru are here'described; also, the name and number of publications, theses, professionalreports, periodicals, articles, books and projects which would betterenhance the profession.